Local Samian Ware Supply in Roman Dacia - Rusu-Bolindeţ, Viorica (Rei Cretariae Romanae Fautorum Acta, 2015)
The production of terra sigillata in Dacia certainly started only after the Roman conquest and gained momentum during the second half of the 2nd century AD, reaching a peak during the Severan era (alongside other pottery categories produced locally). The period under discussion marked, both for Dacia and for other Danubian provinces, a time of maximum economic development, but also with regard to urbanization, the social ascension of local elites (also as a consequence of Caracalla granting the Constitutio Antoniniana), the peak of building activity etc. Despite all these, one notes a decrease in sigillata imports both in Dacia and in the neighboring provinces. This phenomenon is susceptible of several explanations, one being that the activity of the western terra sigillata workshops decreased or even ceased. In the same time the local workshops intensified their activity and started to produce most of the ceramic wares known in the Roman world, including terra sigillata.